Clinical implementation of combined modulated electron and photon beams with conventional MLC for accelerated partial breast irradiation. Issue 1 (July 2017) - Míguez, Carlos; Jiménez-Ortega, Elisa; Palma, Bianey A.; Miras, Hector; Ureba, Ana; Arráns, Rafael; Carrasco-Peña, Francisco; Illescas-Vacas, Ana; Leal, Antonio
Abstract: Purpose: To report the clinical implementation of a novel external beam radiotherapy technique for accelerated partial breast irradiation treatments based on combined electron and photon modulated beams radiotherapy (MERT+IMRT) with conventional MLC. Materials and methods: A group of patients was selected to test the viability of the technique. The prescribed dose was 38.5 Gy, following a hypofractionated schema, and the structures were defined following the NSABP-B39/RTOG-0413 protocol. The plans were calculated with an in-house Monte Carlo based planning system to consider explicitly the particle interactions with the MLC. An ad-hoc breast phantom was designed for a specific QA protocol. A reduced SSD was used for electron beams. Toxicity and cosmetic effects were assessed at every follow-up visit. Results: All the plans achieved the dosimetric objectives and fulfilled the specific quality assurance protocol. Treatment delivery did not entail additional drawbacks for the clinical routine. Moderate or severe grade of toxicity was not reported, and the cosmetic results were comparable to those obtained with other APBI techniques. Conclusions: Results showed that MERT+IMRT with the MLC is a feasible and secure technique, and easy to be extended to other centers with the implementation of the adequate software for planning.